PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN LIPSTIK PURBASARI DI KOTA KENDARI - Asriani, Fanti; kambolong, makmur; Liwaul, Liwaul (Universitas Halu Oleo, 2018)
The purpose of this study is to determine the effect of product quality on lipstiik purbasari purchase decision and the significance of product quality influence on consumer decisions in purchasing purbasari lipstick. In this study using accidental sampling sampling technique that researchers choose who are members of the population who by chance meet with researchers who are considered to provide the necessary information. The data collection techniques used in this study is to use a questionnaire distributed to the respondents as much as 30 respondents. Product quality positively affects the consumer's decision to purchase a purple lipstick product, hence Hypothesis One (H1) is accepted which states that there is a positive influence. the quality of the product against the purchase decision of lipstick purbasari, and reject Hypothesis Zero (Ho) stating that there is no positive effect of product quality on purchasing decision lipstick purbasari. The result of the test of sinifikansi shows that the quality of the product partially significantly influence the purchasing decision of lipstick purbasari, so Hypothesis One (H1) accepted that there is significant influence of product quality to purchase decision of lipstick purbasari, and reject Hypothesis Zero (Ho) there is a significant effect of product quality on purchasing decision of lipstick purbasari.Â